The impact of desflurane and sevoflurane on the intraoperative and early postoperative period in liver transplantation - S. V. Zhuravel; N. K. Kuznetsova; V. E. Aleksandrova; I. I. Goncharova (Трансплантология (Москва))
Background. A pressing issue is the choice of an anesthetic agent for liver transplantation. The mechanism of the organprotective properties of desflurane and sevoflurane is not fully understood. It is important to understand the effects of desflurane and sevoflurane on the severity of ischemia-reperfusion injury of the liver graftAim. To study the effect of desflurane and sevoflurane on the intraoperative and early postoperative period in liver transplantation.Material and methods. The study included 47 patients with liver cirrhosis of various etiologies who underwent cadaveric liver transplantation between February and December 2020. The groups compared in the study included 24 patients who received desflurane and 23 patients who received sevoflurane.Results. There were no statistically significant differences in the effect of desflurane and sevoflurane on hemodynamic parameters, on the need for vasopressor drugs. Episodes of bradycardia and cardiac arrhythmias were significantly more frequent when using sevoflurane. Patients were extubated significantly faster after surgery in the desflurane group. In the early postoperative period, desflurane and sevoflurane did not adversely affect significantly the liver graft function and the degree of its ischemia-reperfusion injury. The groups appeared comparable in rates of using the renal replacement therapy, the incidence of the graft dysfunction development in the postoperative period, and the surgery outcomes.Conclusions. The use of modern inhalation anesthetics desflurane and sevoflurane to maintain anesthesia during liver transplantation does not adversely affect the course of the intraoperative and early postoperative period.